2016
DOI: 10.5009/gnl15404
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Insulin, Ghrelin, Adiponectin, Leptin, Leptin Receptor and Lipocalin-2 in Children with Celiac Disease Who Do and Do Not Adhere to a Gluten-Free Diet

Abstract: Background/AimsThe roles of the many bioactive peptides in the pathogenesis of celiac disease remain unclear. To evaluate the serum concentrations of insulin, ghrelin, adiponectin, leptin, leptin receptor, and lipocalin-2 in children with celiac disease who do and do not adhere to a gluten-free diet (GFD, intermittent adherence).MethodsPrepubertal, pubertal, and adolescent celiac children were included in this study (74 girls and 53 boys on a GFD and 80 girls and 40 boys off of a GFD).ResultsInsulin levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Discrepancies between the above-mentioned reports may indicate a complex relationship between ghrelin and GERD. Theoretically, high ghrelin levels may lead to GERD by increasing the secretion of gastric juice and decreasing its pH or may also result from esophageal wall lesions as a result of the inflammatory process, as in the case of IBD or celiac disease [ 40 , 65 , 66 ]. On the other hand, ghrelin stimulates stomach motility; thus, decreased levels of ghrelin prolong the duration of gastric emptying, which may be conducive to GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies between the above-mentioned reports may indicate a complex relationship between ghrelin and GERD. Theoretically, high ghrelin levels may lead to GERD by increasing the secretion of gastric juice and decreasing its pH or may also result from esophageal wall lesions as a result of the inflammatory process, as in the case of IBD or celiac disease [ 40 , 65 , 66 ]. On the other hand, ghrelin stimulates stomach motility; thus, decreased levels of ghrelin prolong the duration of gastric emptying, which may be conducive to GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the expression of LCN2, the gene that encodes lipocalin-2, is increased in the duodenum of patients with environmental enteric dysfunction, another small bowel enteropathy with histopathologic similarities to celiac disease (12,13). A prior study found no elevation of plasma lipocalin-2 in patients with celiac disease (14). While immunohistochemistry for lipocalin-2 shows staining in small bowel biopsies of children with celiac disease and not in healthy controls, a difference was not found on quantification (13).…”
Section: Introductionmentioning
confidence: 87%
“…On the other hand, excessive sOB-R could inhibit leptin binding to membrane receptors so that leptin failed to play an effective role on reducing caloric intake, increasing energy expenditure as well as evoking GnRH and LH secretion in vivo [28,29]. Prior studies mentioned that sOB-R levels were not directly related to leptin or body fatness, and presumably mediated by other parameters related to nutrition and energy metabolism [26]. Therefore, the plasma sOB-R levels as a potential factor of PCOS independent of leptin and BMI, can be recommended as a novel indicator of PCOS severity.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the serum leptin receptor levels had a correlation with the quantity of the total fat mass has not been confirmed. In the previous studies, researchers demonstrated the significant correlation between serum sOB-R and BMI in a cohort of healthy children and adolescents [26]; and Sun and colleagues showed that the two nonsynonymous SNPs in the LEPR gene were associated with plasma sOB-R levels at the genome-wide significance level, which highlighted and confirmed the role of LEPR as a candidate gene for regulating sOB-R levels [27]. The above conflicting data might reflect variations in the study design and population stratification.…”
Section: Discussionmentioning
confidence: 99%